Performance factors differentiating the game efficiency between top and low ranked professional netball teams in Australasia - Hazam, Nur Syaza Izzati Mohamad (Universiti Sains Malaysia, 2016)
The main objective of this study was to investigate the differences in game structure and playing patterns between Top and Low Ranked netball teams of Australasia. A total of 14 matches were selected including seven matches from the Top Ranked team and seven matches from Low Ranked team. There were 11 game structure variables chosen for this study including centre pass, turnover, interception, defensive rebound, sideline, backline, free pass, penalty pass, toss up, unimpeded shot and goal. Chest pass, two bounce pass, side pass, overhead pass, shoulder pass, lob pass, below shoulder pass and one bounce pass were selected as performance indicators for playing pattern. Independent T-test was used for the comparison of all variables between the Top Ranked and Low Ranked teams. There were statistically significant differences among teams in game structure for interceptions and goals (p<0.05). The ability of the players to execute more interceptions and scoring more goals lead to a change in the outcome of a match towards either winning or losing; thus, affecting the ranking of the team itself. For playing pattern, side pass, two bounce pass, overhead pass, shoulder pass, below shoulder pass, lob pass and chest pass showed a significance difference with (p<0.05) between the Top Ranked and Low Ranked teams. In some of the passes, Top Ranked team executed more of those than Low Ranked team and vice versa. These differences indicate that these two different level teams had different playing patterns which symbolized their team uniqueness. In conclusion, there were differences in the game structures and playing patterns between Top Ranked and Low Ranked teams. This information can be used by coaches and players themselves to improve technical and tactical aspects thus improving their teams’ level internationally.